Coexistence of Perpendicular and Parallel Exchange Bias Effects on Ni/CoO Bilayer - Parlak, U.; Akoz, M. E.; Erkovan, M. (SPRINGER, 2016)
We present exchange bias properties of Ni/CoO bilayer field cooled in parallel and perpendicular directions. Magnetic moments of cobalt atoms in CoO magnetic unit cells are known to be slightly tilted with respect to their easy axes. Coexistence of both is attributed to the tilt of magnetic moments. CoO layer thickness was kept constant in this study, whereas Ni thickness was varied in a range in order to adjust its perpendicular magnetization. MOKE and VSM were exploited to determine their magnetic characteristics. After field cooling, Ni(22 )/CoO(20 ) bilayer exhibited a large exchange bias of 3 kOe in parallel direction and a relatively small (0.5 kOe) in perpendicular direction at 10 K.
Keywords: Magnetron sputtering; X-ray photoelectron spectroscopy; Perpendicular exchange bias; Blocking temperature; Physics